G Protein-Coupled Estrogen Receptor Agonist G-1 Inhibits Mantle Cell Lymphoma Growth in Preclinical Models - Zhou, Lixia; Yu, Tenghua; Yang, Fei; Han, Jingjing; Zuo, Bin; Huang, Lulu; Bai, Xia; Jiang, Miao; Wu, Depei; Chen, Suning; Xia, Lijun; Ruan, Jia; et al. (Frontiers in Oncology, 2021)
Mantle cell lymphoma (MCL) is an aggressive form of non-Hodgkin’s B-cell lymphoma with poor prognosis. Despite recent advances, resistance to therapy and relapse remain significant clinical problems. G-protein-coupled estrogen receptor (GPER)-mediated estrogenic rapid signaling is implicated in the development of many cancers. However, its role in MCL is unknown. Here we report that GPER activation with selective agonist G-1 induced cell cycle arrest, DNA damage, mitochondria membrane potential abnormality, and eventually apoptosis of MCL cell lines. We found that G-1 induced DNA damage and apoptosis of MCL cells by promoting the expression of nicotinamide adenine dinucleotide phosphate oxidase and the generation of reactive oxygen species. In addition, G-1 inhibited MCL cell proliferation by inactivation of NF-κB signaling and exhibited anti-tumor functions in MCL xenografted mice. Most significantly, G-1 showed synergistic effect with ibrutinib making it a potential candidate for chemotherapy-free therapies against MCL.